Web application performance analysis using Angular, React and Vue.js frameworks - Bielak, Konrad; Borek, Bartłomiej; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2022)
The aim of the work is to conduct a performance analysis and, on its basis, to indicate the most user-friendly and fastest operating framework. Three Internet applications have been written to test the speed of operation of selected technologies. Some of the most popular frameworks were analyzed: Angular, React and Vue. Static comparative criteria used in the work are: favorable and generally available documentation, application development, speed of application development, development and support by creators. The practical criteria are the times measured during the execution of the tests. The tests were performed with simple operations using the CRUD (Create Read Update Delete) function. The performance analysis carried out in this way shows the differences between the frameworks. The following developerPersian tools were used for the comparative analysis: Google Analytics, Google Chrome, Mozilla Firefox, Chrome DevTools.